Hedonic Shopping Motivation and Shopping Lifestyle on Fashion Product Purchases (Among Shopee Online Marketplace Users in West Java, With A Case Study in Cirebon City) - Amroni Amroni; Yani Syafei; Umi Narimawati (Eduvest - Journal of Universal Studies, 2024)
This study aims to determine the effect of hedonic shopping motivation and shopping lifestyle on impulse purchases of fashion products among Shopee e-commerce customers partially and simultaneously. The survey was conducted on Shopee e-commerce customers in Cirebon City. The research method used is a quantitative method with a descriptive approach and an indicator measuring instrument on a Likert scale of 1-4. Data collection using a questionnaire method distributed in the form of a google-form consists of 30 statements filled out by 150 respondents. The sampling technique used is purposive sampling technique. Data analysis used validity test, reliability test, multiple linear regression analysis, T test, F test and coefficient of determination. The results showed that partially hedonic shopping motivation variables had a significant effect on impulse buying with a value of 2.948 > 1.976 and a sign of 0.004 < 0.05 and a shopping lifestyle variable had a significant effect on impulsive buying with a value of 3.615 > 1.976 and a sign of 0.000 < 0.05 and the results of the study simultaneously that hedonic shopping motivation variables and shopping lifestyles had a significant effect on impulse buying with a value of 33.929 > 3.06 and a sign of 0.000 < 0.005. R Square value of 0.316 indicates that the percentage of the influence of hedonic shopping motivation and shopping lifestyle on impulse buying is 31.6% and the remaining 68.4% is influenced by other variables not analyzed in this study.